Tinjauan Hukum Islam Terhadap Akad Ijarah Dalam Kepengurusan SIM Melalui Jasa Makelar - Ilhamy, Muhammad Fatah; Fahrullah, (Jurnal Ekonomika dan Bisnis Islam, 2019)
One of the muamalah activities that the Islamic religion advocates is the sale and purchase of goods, both directly and indirectly. Humans are social creatures in which in carrying out muamalah activities need other human help. SIM management can be done directly or indirectly or through a SIM broker. The term broker in Muammalah Fiqh is known as samsarah. In Islamic Law itself there is no law specifically discussing SIM brokers, but some scholars and the community still have pros and cons in the law of SIM broker realm. This research is a descriptive qualitative research that aims to find out how Islamic law reviews in SIM broker transactions. The SIM broker transaction implementation uses the Ijarah contract in its implementation. From the results of the study it can be concluded that SIM broker transactions are not in accordance with Islamic law because the transaction object is classified as one of 7 illegitimate transactions not the substance, namely Rishwah.